2020
DOI: 10.1017/wet.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optimal droplet size for control of Palmer amaranth (Amaranthus palmeri) with acifluorfen

Abstract: Acifluorfen is a nonsystemic PPO-inhibiting herbicide commonly used for POST Palmer amaranth control in soybean, peanut, and rice across the southern United States. Concerns have been raised regarding herbicide selection pressure and particle drift, increasing the need for application practices that optimize herbicide efficacy while mitigating spray drift. Field research was conducted in 2016, 2017, and 2018 in Mississippi and Nebraska to evaluate the influence of a range of spray droplet sizes [150 μm (Fine) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The comparative broadcast treatment was made as a salvage treatment when Palmer amaranth reached a 20‐ to 30‐cm height, and a sequential application was made 14 days after final treatment (DAFT). At time of the initial postemergence application, ten Palmer amaranth plants were measured and marked with paint at the base of the plant to aid identification and location of targeted plants at a later date 26–28 . In the case where there were not ten Palmer amaranth plants in the plot, all Palmer amaranth in the plot were measured and marked.…”
Section: Methodsmentioning
confidence: 99%
“…The comparative broadcast treatment was made as a salvage treatment when Palmer amaranth reached a 20‐ to 30‐cm height, and a sequential application was made 14 days after final treatment (DAFT). At time of the initial postemergence application, ten Palmer amaranth plants were measured and marked with paint at the base of the plant to aid identification and location of targeted plants at a later date 26–28 . In the case where there were not ten Palmer amaranth plants in the plot, all Palmer amaranth in the plot were measured and marked.…”
Section: Methodsmentioning
confidence: 99%
“…There is a correlation between the viability of Amaranthus palmeri seeds and vigor during artificial aging. After 3 years of naturally existing in soils in Nebraska, vigor of Amaranthus palmeri seeds was found to be less than 10% [19,57]; after 5 months of waterflooding, their vigor was found to be 86% [18]. Therefore, Amaranthus palmeri seeds exhibit a certain tolerance to short-term high temperatures and high humid environments [58,59].…”
Section: Effects Of Different Salt Concentrations Onmentioning
confidence: 99%
“…Its diffusion rate has a tendency to accelerate. Due to its strong adaptability and high genetic variability [16], Amaranthus palmeri can grow on farmlands [17], abandoned lands, in deserts [8], river beds [18], garbage dumps and on roadsides [19]. Invasion risk evaluations have shown that Amaranthus palmeri has a high risk of invasion in North China and Central China [10,20,21], which is the main grain producing area of China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, smaller droplets produced by non-AI nozzles (XR and XRC) should provide better efficacy for non-systemic pesticides due to increased coverage (Ennis andWilliamson, 1963, McKinlay et al, 1972); however, previous research on effect of nozzle type on pest control (specifically weed control) has reported varying results on correlation between droplet size and the pesticide efficacy (Shaw et al, 2000, Sikkema et al, 2008, Berger et al, 2014. These contrasting results could be attributed to interactions among pesticide efficacy and other factors such as weed species and density, tillage, and soil type (Franca et al, 2020).…”
Section: Pest Controlmentioning
confidence: 99%